A dose-finding study of once-daily oral telbivudine in HBeAg-positive patients with chronic hepatitis B virus infection - Ching‐Lung Lai; Seng Gee Lim; Nathaniel Brown; Xiao‐Jian Zhou; Deborah Lloyd; Yin-Mei Lee; Man‐Fung Yuen; George Chao; Maureen Myers (2004)
Current therapy for chronic hepatitis B is suboptimal as a result of limited durable response rates, cumulative viral resistance, and/or poor tolerability. Telbivudine has potent antiviral activity against hepatitis B virus (HBV) in vitro and in the woodchuck model and has a promising preclinical safety profile. In this first clinical study of telbivudine, safety, antiviral activity, and pharmacokinetics were assessed in 43 adults with hepatitis B e antigen-positive chronic hepatitis B. This placebo-controlled dose-escalation trial investigated 6 telbivudine daily dosing levels (25, 50, 100, 200, 400, and 800 mg/d); treatment was given for 4 weeks, with 12 weeks’ follow-up. Serum HBV DNA levels were monitored via quantitative polymerase chain reaction. The results indicate that telbivudine was well tolerated at all dosing levels, with no dose-related or treatment-related clinical or laboratory adverse events. telbivudine plasma pharmacokinetics were dose-proportional within the studied dose range. Marked dose-related antiviral activity was evident, with a maximum at telbivudine doses of 400 mg/d or more. In the 800mg/d cohort, the mean HBV DNA reduction was 3.75 log 10 copies/mL at week 4, comprising a 99.98% reduction in serum viral load. Correspondingly, posttreatment return of viral load was slowest in the high-dose groups. Viral dynamic analyses suggested a high degree of efficiency of inhibition of HBV replication by telbivudine and helped refine selection of the optimal dose. In conclusion , these results support expanded clinical studies of this new agent for the treatment of hepatitis B. (Hepatology 2004;40:719-726.)